Nature’s contribution to poverty alleviation, human wellbeing and the SDGs - Mahesh Poudyal; Franziska Kraft; Geoff Wells; Anamika Das; Suman Attiwilli; Kate Schreckenberg; Sharachchandra Lele; Tim Daw; Carlos Torres-Vitolas; Siddappa Setty; Helen Adams; Sate Ahmad; et al. (Scientific Data, 2024)
Abstract Millions of households globally rely on uncultivated ecosystems for their livelihoods. However, much of the understanding about the broader contribution of uncultivated ecosystems to human wellbeing is still based on a series of small-scale studies due to limited availability of large-scale datasets. We pooled together 11 comparable datasets comprising 232 settlements and 10,971 households in ten low-and middle-income countries, representing forest, savanna and coastal ecosystems to analyse how uncultivated nature contributes to multi-dimensional wellbeing and how benefits from nature are distributed between households. The resulting dataset integrates secondary data on rural livelihoods, multidimensional human wellbeing, household demographics, resource tenure and social-ecological context, primarily drawing on nine existing household surveys and their associated contextual information together with selected variables, such as travel time to cities, population density, local area GDP and land use and land cover from existing global datasets. This integrated dataset has been archived with ReShare (UK Data Service) and will be useful for further analyses on nature-wellbeing relationships on its own or in combination with similar datasets.